An observational study of type, timing, and severity of childhood maltreatment and preterm birth. Issue 6 (8th March 2016) - Selk, Sabrina C; Rich-Edwards, Janet W; Koenen, Karestan; Kubzansky, Laura D
Abstract : Background: Childhood maltreatment has been linked to preterm birth (<37 weeks gestation) in some studies, but these findings have been inconsistent, and it remains unclear whether type, timing or severity of maltreatment are associated with risk of preterm birth. The aim of this observational study was to explore type of maltreatment (child and adolescent physical and sexual abuse and harsh parenting) as risk factors for preterm birth. Methods: We examined these associations in a cross-sectional analysis of the Nurses' Health Study II cohort of female nurses. Women completed a questionnaire about experiences of sexual abuse, physical abuse or harsh parenting, along with pregnancy outcomes. Logistic regression models adjusted for relevant covariates including age, race, alcohol and cigarette use during pregnancy, age at menarche, marital status, adult income, body mass index (kg/m 2 ) at age 18, physical abuse in pregnancy, and childhood socioeconomic position. Results: Among 51 434 first births, 4110 were preterm (8% of births). Forced sexual activity in childhood or adolescence was associated with a 22% increased odds of preterm birth (OR=1.22, 95% CI 1.10 to 1.35). Maltreatment involving sexual touch, physical abuse or harsh parenting was not associated with preterm birth in this sample. Conclusions: Women who experience forced sexual activity in childhood or adolescence may have an increased likelihood of delivering preterm in adulthood.